Placobdella costata (Fr. Müller, 1846) (Hirudinea: Glossiphoniidae), a leech species new for Slovenia - Melita Vamberger; Peter Trontelj (Natura Sloveniae)
The glossiphoniid leech Placobdella costata was confirmed in 2006 for the first time in Slovenia at a complex of fish ponds named 'Draga pri Igu' some 10 km south of Ljubljana (Central Slovenia). Up to 15 leeches were found attached to European pond turtles (Emys orbicularis), the main host species.